How Accountability is Being Addressed by NGOs Working with Women in Malaysia : A Situational Analysis - Barley, Lisa Dawn (2011)
Purpose-The purpose of this dissertation is to conduct an analysis of the state of accountability at NGOs that work with women in Malaysia by exploring the perceptions of the management and Board Members of these organisations.